Transcendent realms: immersive environment for live performance - Karasynska, Anastasiia (2024)
The master's thesis project "Immersive Environment for Live Performance" explores the combination of artistic practice of live audiovisual performance and design in immersive spaces. In the context of rapid technological development, the project focuses on the creation of new forms of expression and the exploration of synesthetic experiences through virtual worlds. Practice-based research (PBR) is applied to content development, technical implementation and performance in the immersive environment CAVE using TouchDesigner. Conceptually, the project is inspired by the idea of transcendence and aims to contribute to a new spatial artistic language. The project provides theoretical and practical knowledge in the field of immersive technologies and generative art, offering approaches to the implementation of audiovisual performance and enriching the understanding of transcendence in contemporary art. As a result, the project contributes to the systematization of immersive design methods, advancing the discourse on immersive arts, illustrating the transformative potential of immersive design in contemporary artistic audiovisual expression.